Soul Loss and the Shamanic Story - Berman, Michael (Newcastle upon Tyne : Cambridge Scholars Pub., 2008)
Stories from various cultures and periods of time can be identified which deal with a concept of soul loss that is essentially shamanic. In shamanism, soul loss is the term used to describe the way parts of the psyche become detached when we are faced with traumatic situations. In shamanic terms, these split-off parts can be found in non-ordinary reality and are only accessible to those familiar with its topography. Case studies are presented to show how the way soul loss is dealt with by ind ...
Table of contents; acknowledgements; chapter one; chapter two; chapter three; chapter four; chapter five; chapter six; chapter seven; chapter eight; chapter nine; chapter ten; chapter eleven; chapter twelve; appendix a; appendix b; appendix c; bibliography; index.
Description based on print version record.
Keywords: Shamanism; Soul; Shamanism; Soul; BODY, MIND & SPIRIT / Spirituality / Shamanism; Electronic books